Causal Relationship between Inflation and Unemployment in Indonesia 1986-2018: A Phillips Curve Analysis - Gerry Ganika; Rizky Maulana (Tirtayasa Ekonomika, 2022)
Inflation and unemployment are closely watched indicators in the economy of a country. The consumers in a goods market are willing to get the goods and services at a relatively lower price, or in other words, they expect a low inflation rate. However, if the inflation rate is low, the incentive of producers to produce more is low, and employment will not happen. Therefore, there are trade-off between inflation and unemployment. This phenomenon is called the Phillips curve. This  study  aims  to  analyze the causal relationship  between  inflation  and  unemployment in Indonesia. We use inflation rate and open unemployment rate from 1986-2018 collected from Statistics Indonesia (bps.go.id). We employed the Granger causality method and found that there is no causal relationship, either one-way or two-way, between inflation and unemployment. Further, we analyzed using simple linear regression and found that inflation significantly affects unemployment and vice-versa.